Grassroots Peacemaking: The Paradox of Reconciliation in El Salvador - Velásquez Estrada, Ruth Elizabeth (Social justice, 2014)
The article explores reconciliation between ex-combatants in El Salvador's civil war and attitudes towards such reconciliation by various sectors of Salvadoran society. Topics include state-led reconciliation commissions and the process of publicly addressing human rights violations; social conflict and the influence of causative factors in promoting closure; and re-creating social networks.